Thermal conductivity of donor-doped GaN – investigations with 3-ωand stationary metods - Churiukova, O.; Jeżowski, A.; Stachowiak, P.; Mucha, J.; Perlin, P.; Suski, T.; Trzebiatowski, W. (Хабаршы. Физика сериясы, 2015)
Gallium nitride due to its unique optical properties and therefore possible applications has been attracting much attention of researchers for over one decade. Thermal conductivity is of interest as a key parameter in the design of high-power devices in which gallium nitride is an important element.